Business Organizes : The Early Years in Québec - Thwaites, James (Relations Industrielles / Industrial Relations, 1981)

Labour Studies Research Bulletin - Thwaites, James (Relations Industrielles / Industrial Relations, 1981)
This article reviews the book, "Labour Studies Research Bulletin," by Labour Studies Resource Center.